Evaluation of the mechanical properties of natural asphalt-modified hot mixture - Kök, Baha Vural; Yılmaz, Mehmet; Turgut, Paki; Kuloğlu, Necati (My University, 2012)
The objective of this study is to evaluate the usage of natural asphalt in hot mix asphalt by means of determining the Marshall stability, stiffness modulus, indirect tensile strength, and dynamic creep tests. Natural asphalt, which consist of 17% asphalt fraction and 83% mineral fraction, was obtained from Syrian. The optimum bitumen content was determined to be 1% lower for natural asphalt-modified mixturex compared to control mixtures. The stiffness modulus values of the natural asphalt-modified mixtures were higher than those of the control mixtures. The moisture susceptibility of natural asphalt-modified mixtures and control mixtures were evaluated during different freeze-thaw cycles. The natural asphalt-modified mixtures were not as susceptible as control mixtures to moisture damage. Adding natural asphalt to mixturesremarkably decreased susceptibility to permanent deformation. The result presented here demonstrate the positive effects of using natural asphalt.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Natural asphalt; Stiffness; Moisture damage; Permanent deformation